Sport communication: an analysis of coach roles through instructional communication framework - Dicky Wahyudi; Yun Fitrahyati Laturrakhmi (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2023)
This research aims to identify the coach roles in youth football coaching at ASIFA (Aji Santoso International Football Academy) through an instructional communication framework. This research uses an approach method with two data collection techniques which include: Interviews with ASIFA coaches, and participant observations at ASIFA football coaching. The data analysis technique combines interactive analysis models and the theory of instructional communication. The results of this study showed that the role of coaches at ASIFA in the instructional communication framework can be classified into two types, namely: 1) Coach as communicators-instructors; and 2) Coach as communicator-facilitator. The difference in type has implications for the communication approach used by the coaches, which is mapped into a rhetorical approach and a relational approach. However, the type of coaches and the communication approach used by the coaches has a relationship with the coaching context that occurs. This research contributes to the formulation of an instructional communication quadrant model that can be carried out by coaches in youth football coaching.